Native plants from the genus Vaccinium in Colombia and their potential uses. A review - Magnitskiy, Stanislav (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2023)
The Andean Region of Colombia has a large variety of species with diverse ethnobotanical uses, including industrial, medicinal and food uses. Among these plants are several wild species from the genus Vaccinium, which are native to the mountainous regions of the country. This review deals with potential uses for agraz (V. meridionale) and agracejo (V. floribundum) in Colombia, focusing on the nutritional potential of these plants and their importance for food security in terms of products made from their fruits and leaves. In addition, this review looks at possible negative effects from anthropic activities and climate change on wild plants from the genus Vaccinium.